The use of building information modeling to achieve the sustainability of residential buildings (lighting case study) - ابراهيم, مايا; جمال عمران, (Latakia University Journal -Engineering Sciences Series, 2023)
Energy is one of the most important issues that attracts the attention of the whole world, although the interest in it is still very limited. Among them is to reduce energy demand, as energy consumption in buildings represents about 40% of global energy use, as energy consumption is increasing rapidly all over the world. The research aims to study the importance of using Building Information Modeling (BIM) in analyzing the energy of residential buildings in general and natural lighting in particular. To study the daylight coefficient for the different areas within the building using (Ecotect). Then calculating the amount of incoming radiation using the (Insight) program to enable us to calculate the amount of solar radiation that enters through windows and doors, Where three cases were assumed for the dimensions of windows and doors, and the amount of solar radiation entering through them was studied, and then all these results were compared for the three cases and the different floors. It was also obtained through (Ecotect) programs the amount of industrial electric lighting, where the savings percentages were calculated for each case Of the studied cases, the results indicated that the percentage of savings in the first case was 38%, 44.5% for the second case, and 49% for the third case, as well as the use of visual modeling by (Dynamo) in estimating the cost of each modification and its reflection on the cost for the three studied cases.